Leadership and community healthcare reform: a study using the Competing Values Framework (CVF). Issue 4 (5th August 2021) - O'Neill, Debra; De Vries, Jan; Comiskey, Catherine M.
Abstract : Purpose: The Health Service Executive in Ireland seeks to further develop healthcare in the community. It has identified that this reform requires developing leadership amongst the staff. This study aims to identify what kind of leadership staff in community healthcare observe in practice and their leadership preferences. The core objective has been to identify the readiness of the organisation to implement the adopted national policy of integrated community care reform in terms of leadership development. Design/methodology/approach: An online cross-sectional survey was conducted using the Organisational Cultural Assessment Instrument, based on the Competing Values Framework. This tool identifies four overarching leadership types: Clan (Collaborative), Adhocracy (Creative), Market (Competitive) and Hierarchy (Controlling). Participants (n = 445) were a representative sample of regional community health care employees. They were asked to identify presently observed leadership and preferred leadership in practice. The statistical analysis emphasised a comparison of observed and preferred leadership types. Findings: Participants reported the current prevailing leadership type as Market (M = 34.38, SD = 6.22) and Hierarchical (M = 34.38, SD = 22.62), whilst the preferred or future style was overwhelmingly Clan (M = 40.38, SD = 18.08). Differences were significant (all p 's < 0.001). The overall outcome indicates a predominance of controlling and competitive leadership and a lack of collaborative leadership to implement the planned reform. Originality/value: During reform in healthcare, leadership in practice must be aligned to the reform strategy, demonstrating collaboration, flexibility and support for innovation. This unique study demonstrates the importance of examining leadership type and competencies to indicate readiness to deliver national community health care reform.